Sequential and Multistep Substrate Interrogation Provides the Scaffold for Specificity in Human Flap Endonuclease 1 - Sobhy, Mohamed A.; Joudeh, Luay I.; Huang, Xiaojuan; Takahashi, Masateru; Hamdan, Samir M. (Cell reports (Cambridge), 2013)
Human flap endonuclease 1 (FEN1), one of the structure-specific 5′ nucleases, is integral in replication, repair, and recombination of cellular DNA. The 5′ nucleases share significant unifying features yet cleave diverse substrates at similar positions relative to 5′ end junctions. Using single-molecule Förster resonance energy transfer, we find a multistep mechanism that verifies all substrate features before inducing the intermediary-DNA bending step that is believed to unify 5′ nuclease mechanisms. This is achieved by coordinating threading of the 5′ flap of a nick junction into the conserved capped-helical gateway, overseeing the active site, and bending by binding at the base of the junction. We propose that this sequential and multistep substrate recognition process allows different 5′ nucleases to recognize different substrates and restrict the induction of DNA bending to the last common step. Such mechanisms would also ensure the protection of DNA junctions from nonspecific bending and cleavage. [Display omitted] •Single-molecule FRET reveals dynamics of FEN1 substrate recognition•FEN1 binds downstream dsDNA, threads 5′ flap, engages 3′ flap, and bends DNA•FEN1 unstructured to structured transition couples 5′ flap threading and DNA bending•FEN1 substrate verification explains the substrate specificity observed for 5′ nucleases Structure-specific 5′-nucleases are integral to all aspects of DNA metabolism. They share significant unifying structural features yet cleave diverse substrates at similar positions relative to 5′-end junctions. DNA bending at the 5′-end junction solves this geometrical puzzle by unifying their cleavage mechanism. Using flap endonuclease-1, Hamdan and colleagues reveal a multistep mechanism that verifies all substrate features before committing to DNA bending. They propose that 5′-nucleases recognize their different substrates in a sequential and multistep manner that restrict the induction of DNA bending.